Implementation of Government Regulation No. 53 of 2010 concerning Civil Servant Discipline in the Finance, Asset, and Revenue Management Office of Minahasa Regency - Masengi, Evi Elvira; Lumingkewas, Elvis M. C.; Supit, Brain Fransisco (Technium Social Sciences Journal, 2023)
This study aims to 1) find out, analyze and describe the Implementation of Government Regulation No. 53 of 2010 concerning Discipline for Civil Servants in the Finance, Asset, and Revenue Management Office of Minahasa Regency, 2) To find out, analyze and describe what factors influence the Implementation of Regulations Government No. 53 of 2010 concerning Discipline for Civil Servants at the Office of Finance, Assets and Revenue Management of Minahasa Regency. The research method used is qualitative research with a purposive sampling technique. The research location is the Minahasa Regency Office of Finance, Assets, and Revenue Management. Data collection techniques are observation, interviews, and documentation which are then analyzed through data reduction, data presentation, and conclusion. The results of the study show that 1) Policy implementation of Government Regulation No. 53 of 2010 concerning Civil Servant Discipline at the Office of Financial Management, Assets and Regional Revenue of Minahasa Regency has not gone well, which is influenced by two things, namely the implementation of the policy is still not good and the environmental conditions of the policy are not supportive. 2) Factors influencing the implementation of the policy of Government Regulation No. 53 concerning the Discipline of Civil Servants at the Office of Finance, Assets and Revenue Management of the Minahasa Regency are a) socialization of the policy is still weak so that Civil Servants do not understand the policy, b) the mentality of Civil Servants is still not good which resulted in not optimal care, awareness and responsibility towards the agency, c) there was no good example from the leadership, d) the implementation of Rewards and Punishment was still unclear and not firm, e) there were differences in treatment from superiors to subordinates because of closeness relationship (favouritism factor), f) no clear job description.